Lepton masses and mixing and lepton number violating processes in the minimal 3-3-1 model - Machado, A. C. B. [UNESP]; Montano, J. [UNESP]; Pleitez, V. [UNESP]; IOP (Iop Publishing Ltd, 2017)
We consider the minimal 3-3-1 model with sterile neutrinos transforming as singlet under the SU(3)(L) circle times U(1)(X) symmetry and we find numerical solutions for these matrices by imposing that besides the observed lepton masses, they also give the observed mixing matrix in the lepton sector, the so called Pontecorvo-Maki-Nakawaga-Sakata (PMNS) matrix. After that we study its phenomenological consequences in various processes involving flavor number violating interactions. In the allowed leptonic decays l(i) -> l(j)l(k)(l) over bar (k) which occurs at the tree level with l(i) = mu, tau, l(j,k) = e, mu, we find in particular that the channel mu -> ee (e) over bar imposes a lower mass limit on the vector doubly charged bilepton of 4.58 TeV and that the scalar contributions are negligible.